2 Cardiac Resynchronisation Therapy Leads to Reversal of Heart Failure Induced Sarcopenia. (3rd June 2016) - Warriner, David; Webb, Philip; Sheridan, Paul; Lawford, Patricia
Abstract : Background: Sarcopenia, a reduction in skeletal muscle performance, is common in heart failure (HF) and grip strength (GS) is a measure of such. No trial has investigated the role of cardiac resynchronisation therapy (CRT) in reversing sarcopenia. Methods: GS was measured at baseline and 12 months following CRT. The patient group were 94% male, mean age 69 ± 8 years, New York Heart Association (NYHA) functional class II-IV, QRSd 173 ± 21 ms and had a left ventricular ejection fraction (LVEF) 26 ± 8%. Results: 70% of patients were found to have responded at 12 months. Responders had significant improvements in VO2 (12.6 ± 1.7 to 14.7 ± 1.5 ml/kg/min, p < 0.05), quality of life score (43 ± 23 to 24 ± 22, p < 0.01), left ventricular end diastolic volume (210 ± 125 ml to 173 ± 125 ml, p < 0.01), 6 min walk distance (379 ± 117 m at baseline to 418 ± 105 m ( p < 0.05) and N-terminal pro-B-type natriuretic peptide (2422 ± 829 to 1732 ± 976 pg/ml, p < 0.01). GS significantly increased, by over 18% in responders during follow-up. Conclusion: This study demonstrates responders demonstrate a significant improvement in GS following CRT. This demonstrates that CRT improves not only cardiac performance but also secondary gains in skeletal muscle function.